Osteoprotegerin is Secreted Into the Coronary Circulation: A Possible Association with the Renin-Angiotensin System and Cardiac Hypertrophy - Koyama, S.; Tsuruda, T.; Ideguchi, T.; Kawagoe, J.; Onitsuka, H.; Ishikawa, T.; Date, H.; Hatakeyama, K.; Asada, Y.; Kato, J.; Kitamura, K. (Hormone and Metabolic Research, 2014)
The circulating osteoprotegerin (OPG) level reflects a series of cardiovascular diseases; however, the source(s) of circulating OPG remain(s) to be determined. This study explored whether OPG is released in the coronary circulation and whether it is associated with cardiac structure and function. Fifty-six patients (67±10 years old, male 57%, hypertension 73%, coronary artery disease 50%) were enrolled, and blood samples were collected simultaneously from the orifice of the left coronary artery (CA) and the coronary sinus (CS) after angiography. The concentration of OPG was higher in the CS than in the CA (7.7±4.1 vs. 6.7±3.6 pmol/l, p<0.001). The trans-cardiac OPG concentration was significantly (p=0.019) decreased in patients who have been prescribed either an angiotensin converting enzyme inhibitor or an angiotensin II type 1 receptor blocker (ACEI/ARB). In patients subgroup who did not take an ACEI/ARB (n=27), the trans-cardiac OPG level was positively correlated with age (r=0.396, p=0.041) and relative wall thickness of left ventricle (r=0.534, p=0.004). In multivariate linear regression analysis, relative wall thickness remained to be the independent variable for the trans-cardiac OPG level (p=0.004). Moreover, trans-cardiac OPG was significantly (p=0.021) increased in patients with relative wall thickness greater than 0.45 but it did not differ if the left ventricular mass index was increased (≥116 for males, or ≥ 104 for females, g/m2) or not (p=0.627). This study suggests that OPG is secreted into the coronary circulation and is associated with concentric remodeling/hypertrophy of LV, possibly in interactions with the renin-angiotensin system.
Keywords: angiotensin II; concentric hypertrophy; remodeling